2024
DOI: 10.1039/d3qi02145a
|View full text |Cite
|
Sign up to set email alerts
|

Organelle imaging with carbon dots: strategies, challenges, and perspectives

Quanxing Mao,
Yujie Meng,
Yuhang Feng
et al.

Abstract: Organelle imaging is an efficient approach to gain information about intracellular events and dynamics of subcellular structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 160 publications
0
0
0
Order By: Relevance
“…110 It is pertinent to note that understanding the cellular uptake pathways of CDs is crucial for assessing their biological properties and optimizing their biomedical applications. 25…”
Section: Applicationsmentioning
confidence: 99%
See 3 more Smart Citations
“…110 It is pertinent to note that understanding the cellular uptake pathways of CDs is crucial for assessing their biological properties and optimizing their biomedical applications. 25…”
Section: Applicationsmentioning
confidence: 99%
“…However, it has been reported that CDs synthesized from identical precursors and uniform conditions were shown to exhibit diverse organelle-targeting properties. 25 As a result, further comprehensive studies focusing on preparation methodologies are vital to enhance the organelle selectivity of intrinsic nucleolus-targeting CDs.…”
Section: Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…As a new type of nanomaterial, carbon dots (CDs) are usually spherical particles with a particle size of less than 10 nm, and have good water solubility, 13 photoluminescence, 14 easy regulation, 15 low toxicity, 16 and biocompatibility. 17,18 CDs have been widely used in cosmetics, 19 cell imaging, 20 sensing, 21 information encryption, 22 and other fields. Researchers have shown great interest in the multi-functionalization of CDs and have begun to explore and apply it in the fields of agriculture.…”
Section: Introductionmentioning
confidence: 99%